STIMULASI PERTUMBUHAN BIBIT TEH (Camellia sinensis) DENGAN PEMBERIAN URIN SAPI DAN PENGGUNAAN BAHAN STEK YANG BERBEDA - Noni Fatmala; Hermansyah Hermansyah; Marlin Marlin (BPFP Universitas Bengkulu, 2020)
[STIMULATION EFFECTS OF BIOURINE CONCENTRATION AND THE STEM SEGMENT OF CUTTINGS ON GROWTH OF TEA (Camellia sinensis) SEEDLINGS]. Tea seedlings can be prepared by the stem segment cutting and provide treatment to stimulate the growth of cuttings. This study aims to determine the optimal tea seedlings growth from different material of stem segment and biourine concentration. The experiment was conducted in February to June 2020 at PT. Sarana Mandiri Mukti Kelurahan Tangsi Baru, Kabawetan District, Kepahiang Regency, Bengkulu Province. This research uses factorial completely randomized design (CRD) with two factors. The first factor, biourine concentration consisting of 5 levels including 0%, 25%, 50%, 75%, 100%. The second factor, the stem segment of cuttings consisting of 3, 4, and 5 segments. The treatment was repeated 3 times, with 5 plants sample in each treatment. There was totally 225 plants. The results showed that biourine concentration of 100% has significantly different from the variable roots number and root length. The stem segment of the tea cuttings has no significantly difference effect on all variables. The interaction between biourine concentration and stem segment of the tea cuttings has significantly different in variables of shoot length and seedlings fresh weight. The optimum growth of tea seedling was obtained in stem cutting of 3 segment and application of biourine concentration of 100%.